Al-Azim mosque Pandan Indah and Its Contributionin Islamic Da'wah - Muhammad Shahril Bin Mohd Nor (Kolej Universiti Islam Malaysia, 2011)
Author has chosen the title of "Islamic Neighborhood Concept and Its Relation With Society At Kampung Rambai", to study the real practice of neighborhood in current society. In this study, author also attempting to discover the real meaning of Islamic neighborhood. Author also studying the actual practice of neighborhood concept, and at what level the Islamic value is practiced in local community. Author used observation method in order to gain related information. Author also got the data through book reading, magazines, Internet and etc. The study showed the current practice of neighborhood ness is in parallel with Islam.